Antibacterial and anticancer potential of bioactive compounds and secondary metabolites of endophytic fungi isolated from Anethum graveolens - El-Zehery, Hoda R. A.; Ashry, Noha Mohamed; Faiesal, Abeer A.; Attia, Mohamed S.; Abdel-Maksoud, Mostafa A.; El-Tayeb, Mohamed A.; Aufy, Mohammed; El-Dougdoug, Noha K. (Frontiers in Microbiology, 2024)
Fungal endophytes are known to produce bioactive chemicals and secondary metabolites that are often identical to those produced by their host plants. The main objective of the current study was to isolate and identify endophytic fungi associated with the medicinal plant Anethum graveolens, and to investigate their potential antibacterial and anticancer properties. The ethyl acetate extracts from the isolated endophytic fungi, as well as the host plant A. graveolens, were subjected to bioactivity assays to evaluate their antibacterial and anticancer potential against multi-drug resistant bacterial strains and the human hepatocellular carcinoma cell line HepG2. The endophytic fungi isolated and identified from the A. graveolens samples included Diaporthe, Auxarthron, Arthrinium, Aspergillus, Microsporum, Dothiorella, Trichophyton, Lophiostoma, Penicillium, and Trichoderma species. The minimum inhibitory concentration (MIC) assay revealed that the A. graveolens extract exhibited the strongest antibacterial activity, with an MIC value of 4 μg/mL, followed by the Trichoderma sp. (5 μg/mL) and Penicillium sp. (6 μg/mL) extracts. Additionally, the crude extracts of Trichoderma sp., Penicillium sp., and Fusarium sp. demonstrated high anticancer activity against HepG2 cells, with inhibition rates ranging from 89 % to 92 % at a concentration of 50 μg/mL. Interestingly, the A. graveolens extract showed the most potent anticancer activity, with a 95% inhibition rate against HepG2 cells at the same concentration. These findings highlight the significant potential of endophytic fungi associated with A. graveolens, as a source of bioactive compounds with promising antibacterial and anticancer properties. The results reinforce the hypothesis that medicinal plants and their endophytic fungi can serve as an attractive alternative for the development of novel therapeutic agents, potentially offering a more sustainable and less harmful approach to disease management compared to traditional chemical-based methods.